2002
DOI: 10.1159/000050089
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Epitopes on the Fiber Knobs of Human Adenovirus Serotypes 8 and 15

Abstract: In order to obtain information on the linear antigenic epitopes on fiber knobs of adenovirus serotypes 8 (Ad8) and 15 (Ad15) of subgenus D, the binding of polyclonal virus- and fiber-specific rabbit antibodies to overlapping peptides covering the fiber knob was studied. The main antigenic epitopes of the fiber knob of Ad8 (FK8) were represented by the peptides P4 [amino acids (aa) 213–227], P6 (aa 233–247), P11 (aa 283–297), P13 (aa 303–317) and P15 (aa 316–325); the peptides P1 (aa 183–197), P8 (aa 253–267), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…3) Phage-mediated depletion of RGD-and other epitope-directed Pb antibodies. In order to determine the contribution of anti-RGD antibody in Ad vector NA, the unique phage carrying the epitope RGDVTF was amplified and incubated with 17 different serum samples which had Pb antibodies and moderate to high Ad NA titers (D10 samples from patients 1, 2, 3, 4, 5, 6, 7, 8, 9, 11, 12, 14, and 16 and samples 18,19,20, and 21 from healthy donors). After removal of the phage (RGD)-antibody complexes by centrifugation, the serum supernatants were tested for Ad NA, which were indirectly assayed by their effect on gene transduction by using the Ad5Luc3 vector.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) Phage-mediated depletion of RGD-and other epitope-directed Pb antibodies. In order to determine the contribution of anti-RGD antibody in Ad vector NA, the unique phage carrying the epitope RGDVTF was amplified and incubated with 17 different serum samples which had Pb antibodies and moderate to high Ad NA titers (D10 samples from patients 1, 2, 3, 4, 5, 6, 7, 8, 9, 11, 12, 14, and 16 and samples 18,19,20, and 21 from healthy donors). After removal of the phage (RGD)-antibody complexes by centrifugation, the serum supernatants were tested for Ad NA, which were indirectly assayed by their effect on gene transduction by using the Ad5Luc3 vector.…”
Section: Resultsmentioning
confidence: 99%
“…The sera of the patients before and after Ad administration were analyzed for their NA effect on Ad infection, and their reactivity against the three major Ad capsid proteins: hexon, fiber, and Pb. Several research groups have shown Ad capsid epitopes in hexon (5,32) and fiber (6,(19)(20)(21) proteins that were responsible for the immune response. However, the immunogenicity in humans and the characterization of neutralizing and nonneutralizing epitopes in the third major Ad capsid component, the Pb, has not been systematically studied.…”
mentioning
confidence: 99%
“…This is not so surprising. Analysis of the regions that are highly conserved among human adenovirus serotypes [78][79][80]107] suggests that CAV-2 shares some conserved antigenic epitopes. The question is how many different antigens need to be present before it becomes problematic in the clinic.…”
Section: Pre-existingmentioning
confidence: 99%
“…Many previous studies have mapped linear epitopes on the fiber knobs of Ad2, Ad3, Ad5, Ad8 and Ad15, and several type-specific antigenic epitopes on the knob can be identified by ELISA and other methods (Fender et al, 1995;Liebermann et al, 1998Liebermann et al, , 2001Liebermann et al, , 2002. However, few studies have been carried out to identify the neutralization epitopes on the AdV fiber knob.…”
Section: Introductionmentioning
confidence: 99%